2013
DOI: 10.1073/pnas.1218341110
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in voltage-sensor charge and electromotility imply slow chloride-driven state transitions in the solute carrier SLC26a5

Abstract: Outer hair cells (OHCs) drive cochlear amplification that enhances our ability to detect and discriminate sounds. The motor protein, prestin, which evolved from the SLC26 anion transporter family, underlies the OHC's voltage-dependent mechanical activity (eM). Here we report on simultaneous measures of prestin's voltagesensor charge movement (nonlinear capacitance, NLC) and eM that evidence disparities in their voltage dependence and magnitude as a function of intracellular chloride, challenging decades' old d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 62 publications
8
40
1
Order By: Relevance
“…S1 (guinea pig parameters) and Fig. S2 (mouse parameters) show that each method of R s correction gives the same results, revealing the intrinsic low pass eM response of the meno presto model that derives from its stretched-exponential intermediary transition kinetics (Song and Santos-Sacchi, 2013; Santos-Sacchi and Tan, 2018).…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…S1 (guinea pig parameters) and Fig. S2 (mouse parameters) show that each method of R s correction gives the same results, revealing the intrinsic low pass eM response of the meno presto model that derives from its stretched-exponential intermediary transition kinetics (Song and Santos-Sacchi, 2013; Santos-Sacchi and Tan, 2018).…”
Section: Methodsmentioning
confidence: 72%
“…Models were implemented in MATLAB Simulink and Simscape, as detailed previously (Song and Santos-Sacchi, 2013; Santos-Sacchi and Song, 2014b). Model R s and R m were from the averages of guinea pig and mouse OHC parameters obtained (see below).…”
Section: Methodsmentioning
confidence: 99%
“…They showed that prestin-associated charge movement and the resulting electromotility are fully coupled and that prestin has at least two voltage-dependent conformational transition steps. While tight coupling of motility and NLC was also demonstrated in a recent study (Song and Santos-Sacchi, 2013), intracellular Cl − concentration can significantly modulate the coupling.…”
Section: Molecular Mechanism Of How Prestin Workmentioning
confidence: 53%
“…Considerable progress has been made in recent years in our understanding of the mechanism of prestin-based somatic motility, or "electromotility," of outer hair cells (OHCs) in the cochlea, both on cellular- [1][2][3] and the molecular levels [4][5][6], as well as clarifying its physical basis that it is based on electromechanical coupling [7][8][9]. For example, experiments on isolated OHCs have determined load-free displacement [1,2] and isometric force production [10,11].…”
Section: Introductionmentioning
confidence: 99%